"Contingent organisation" on the East Rand : new labour formations organising outside of trade unions, CWAO and the workers' Solidarity Committee. - Zuma, Nkosinathi Godfrey (My University, 2016)
This research paper studied the recent labour unrest in the East Rand as there has been a rise in the number of marches and demonstrations led by the precarious workers to several workplaces. [No abstract provided. Information taken from introduction]
Research report for the degree of Master of Arts in Industrial Sociology, submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg
Keywords: Labor unions--South Africa; Labor movement--South Africa; Labor disputes--South Africa; Strikes and lockouts--South Africa